Exploring parenthood intentions and perceptions of infertility and assisted reproductive technology among 2SLGBTQIA + young adults in Ontario, Canada: a mixed methods study - Caitlin I. T. Ennis; Nurasha G. Fernando; Karen P. Phillips (Journal of Health, Population and Nutrition)
Abstract Background As Generation Z two-spirit, lesbian, gay, bisexual, transgender/trans, queer, intersex, asexual and others who identify as part of sexual and gender diverse communities (2SLGBTQIA +) enter adulthood, contemplation of family creation may be challenged by biological and/or social infertility. Despite some advances in societal acceptance of gender and sexual minorities, family planning and reproductive healthcare remain heteronormative. To explore reproductive decision-making and how future families are conceptualized across genders, we evaluated perceptions of Ontario, Canada non-parenting, 2SLGBTQIA + emerging adults. Methods An online survey, designed as mixed-methods with sex-and-gender-based analysis (SGBA +), was used to recruit childless, post-secondary students, aged 18–30 years, in May–October 2022. Survey questions were analyzed by descriptive statistics across gender groups. Open-text responses were analyzed by thematic and content analysis. Results Parenthood intentions, conceptualizations of future family and perceptions of ART were described by 286 2SLGBTQIA + individuals, who were primarily Caucasian, cis women (69.2%), identified as bisexual-pansexual (66.4%), and belonged to Generation Z (85%). Only 33.9% of the sample definitively wanted children, with 33.6% unsure, and 32.5% preferring to remain childless. Themes describing participants’ future family visions included: (i) committed partners are family, (ii) family includes children (subtheme: adoption/fostering as options for family creation), (iii) family values include love and acceptance, (iv) chosen families, and (v) families can be childfree. ART was acceptable in the event of future infertility, with two major themes used to describe perceived barriers to ART: (i) treatment is expensive; and (ii) I may face discrimination due to my gender identity/sexual orientation. Trans men were significantly more worried about healthcare access to have a biological child (86.7%; χ2(3):16.805 p < .001) than other genders. Conclusions 2SLGBTQIA + respondents expanded the rigid, heteronormative nuclear family model to envision families comprised of partners, biological and adoptive/foster children, friends and chosen family. Participants across genders recognized systemic 2SLGBTQIA + discrimination, with transgender/trans respondents particularly concerned about barriers to reproductive healthcare. A better understanding of reproductive decision-making by 2SLGBTQIA + individuals can contribute to more equitable and inclusive ART healthcare.